Retrocaval ureter: about an observation with successful plastic correction - Mendy Noriega, Fabián; Pereira, Rubi; Benquet, Gabriel; Pereyra Bonasso, Jorge (Cirugía del Uruguay, 1974)
By default, in this work published in the previous issue of the Journal, the discussion was interrupted. We intend to correct the error playing the omitted part.